Snow Leopard (Uncia uncia), Prey Species and Outreach in Langtang National, Park, Nepal - Chalise, M.K. (Our Nature, 2012)
Presence of snow leopard (Uncia uncia) in Langtang National Park was obscure till 2003. It was confirmed by a research team trained for the wildlife biology in the field. Along with the study of ecology and behavior of snow leopard sufficient effort were made to generate data on pre species. The study also dealt with threat perceived for the leopard survival while basic unit of conservation- local outreach programs were also initiated. DOI: http://dx.doi.org/10.3126/on.v9i1.5744